Analysis of MHD tangent hyperbolic hybrid nanofluid flow with different base fluids over a porous stretched sheet - Vishalkumar J. Prajapati; Ramakanta Meher (Journal of Taibah University for Science)
This study investigates the flow of a two-dimensional magnetohydrodynamic(MHD) tangential hyperbolic hybrid nano fluid flow towards a porous stretched sheet with an inclined magnetic field under velocity and thermal slip conditions. Two distinct base fluids, (i) water and (ii) a mixture of [Formula: see text] ethylene glycol([Formula: see text]) and [Formula: see text] water are employed as base liquids with Copper([Formula: see text]) and aluminium oxide([Formula: see text]) nanoparticles, to generate two different hybrid nanofluids as [Formula: see text] and [Formula: see text]. Scaling group transformations with a homotopy algorithm is used to study the effects of distinct physical parameters like the Weissenberg number, an inclined magnetic field, thermal radiation, velocity, and thermal slip conditions with a heat generation/absorption parameter and a permeable parameter on the velocity and temperature distributions. The outcomes of [Formula: see text] hybrid nano fluid are compared with [Formula: see text] hybrid nano fluid in significant critical physical circumstances using graphs and tables. It is observed that the parameters [Formula: see text] and [Formula: see text], [Formula: see text], and λ increase the fluid temperature and decelerate the motion of fluid. The obtained results are validated by comparing them with the existing literature and found that the present results are consistent with the given data. Additionally, it is also noticed that the [Formula: see text] hybrid nanofluid has a higher heat transmission rate as compared to [Formula: see text] hybrid nanofluid. Finally, the impact of nano particle volume fractions of copper and aluminium oxide on the velocity and temperature profiles is discussed to study their efficiency.